On the question of raising the level of competitiveness of the industry of Kazakhstan civil aviation. (Journal of Economic Research & Business Administration, 2015)
The article examines the state of the Republic of Kazakhstan civil aviation industry, the importance of transport - communication complex to enhance the competitiveness of the economy, highlights the Transport Strategy of Kazakhstan till 2015, revealed its specificity and are the main activities of its implementation also addresses the main problems faced by the Republic of Kazakhstan aviation. After considering these questions, the author comes to the conclusion that the civil aviation of Kazakhstan at the present stage is a steadily growing industry, which has all the prerequisites for a successful integration into the global transport and communications system.